Strategies for Developing Arabic Speaking Skills (Maharah Kalam) at Private Islamic Senior High School: A Descriptive Qualitative Study - Erka Pulungan; Lia Mahardika Harahap; Aidil ’Azza Mu’izzuddin; Hadi Mar’i Zain; Hakmi Wahyudi; Siti Sumaiah; Nurul Mardhatillah (Universitas Islam Negeri Palopo, 2026)
Arabic speaking proficiency (maharah kalam) remains a central challenge in Islamic educational institutions in Indonesia. While communicative strategies have been widely discussed theoretically, few studies have examined their systematic implementation in specific madrasah contexts. This study investigates the strategies employed in the Arabic language learning programme at Private Islamic Senior High School Medan to develop students’ maharah kalam, with particular attention to the role of the language environment (bi’ah lughawiyah). Using a descriptive qualitative approach, data were collected through classroom observations, interviews with Arabic teachers and students, and documentation analysis. Findings reveal that the key strategies implemented include muhadasah (conversation) practice, daily vocabulary provision, dialogue and role-play exercises, and the creation of an Arabic-immersive school environment. The language environment (bi’ah lughawiyah) emerged as the most influential factor in improving speaking fluency, as it provided students with continuous communicative practice beyond formal classroom instruction. Supporting factors included teacher creativity and extracurricular language activities, while the main inhibiting factors were limited student vocabulary and low self-confidence. The study concludes that communicative, practice-oriented strategies embedded within an active language environment are effective in gradually improving maharah kalam. These findings contribute practical insights for Arabic language educators and Islamic educational institutions aiming to design more effective speaking-focused learning programmes.